Female Political Youth Activism. A Study of the Motivation in Seke - Dodo, Obediah; Mpofu, Blessmore (PARTECIPAZIONE E CONFLITTO, 2019)
The study seeking to understand the participation of female youth in active politics in Zimbabwe was influenced by the desire in some of the female youth to participate actively only to face unending challenges socially, politically and economically. The study was conducted in the form of a survey using questionnaires administered to 200 participants purposively sampled in Chitungwiza’s four residential Units with each contributing 50 female participants. Analysis of data was conducted using ’Framework’, a qualitative analytic method which assisted to comprehend internal meanings of the participants’ responses and presenting them qualitatively. The study established that while Zimbabwe has various instruments for the promotion of women involvement in politics, the political terrain is defined by several social, economic and cultural barriers. The study identified some of the factors driving female youth into politics and some hindering their participation. It was established that areas with higher levels of election-related persecution are more exposed to politics and higher levels of wanting to participate in political developments. It was noted that female youth who had experienced violence are more probable than non-affected youth to turn out to be effective politicians and to realise the importance of elections.